Efeitos da terapia anti-inflamatória não esteroidal sobre a função renal durante o pós-cirúrgico de caninos submetidos à ovario-histerectomia eletiva - Amaral, Bruna Portolan (2016)
Renal diseases are important in human and veterinary patients and may have different causes, such as infections, toxic agents and renal ischemia. The present work aimed to evaluate the potential of two nonsteroidal anti-inflammatory drugs (NSAIDs), meloxicam and ketoprofen, to cause kidney injury and the ability to early detect renal changes by laboratory methods. 30 healthy bitches were divided into three groups and underwent ovariohysterectomy. The groups were treated as follows: meloxicam (group 1, GM), ketoprofen (group 2, GK), and tramadol monohydrate (group 3, GT). Blood and urine samples were collected from each animal before (M0), 24, 48 and 72 hours after surgery. Blood samples were used for complete blood count (CBC) and serum determination of blood ureic nitrogen (BUN) and creatinine concentration. The clinical evolution was also assessed. Urine analysis and ureic nitrogen, creatinine and protein concentrations were also biochemically determined in urine samples. Protein/Creatinine ratios (PCR) and fractionated excretion of creatinine were calculated. No difference was observed in regard to clinical outcome, water or food intake, diuresis and wound healing between the groups. Considering serum creatinine and BUN, there was an increase in all post-operative moments in GK and a decrease in urinary ureic nitrogen and creatinine, indicating a reduction in glomerular filtration rate (GFR). The results of protein excretion showed an increase of 207% in PCR in GM. This increase was seen only in GM and at 24 hours and remained increased until 72 hours. Increased PCR can be related to an increased permeability of the glomerular membrane leading to proteinuria in this group. However, the values observed are defined as borderline when evaluating proteinuria. The obtained results demonstrate that ketoprofen and meloxicam administered to animals submitted to surgery can change GFR and protein renal excretion, respectively and should be avoided in animals with risk of developing renal diseases. Serial evaluation of serum and urinary levels of ureic nitrogen and creatinine, as well as the PCR were effective in detecting alterations in renal function. The similar clinical outcome between the groups suggests that after surgeries with low complexity and minor tissue manipulation, only analgesia may be sufficient, and is indicated in order to avoid further kidney dysfunction.